Development of a Method for Characterizing Joint Stiffness, Deadband, and Hysteresis - G.D. Ferney; S.L. Folkman (Shock and Vibration)
This article documents the development of a procedure for characterizing the stiffness, deadband, and hysteretic behavior of struts with pinned joints. A test setup utilized procedures recommended by other authors. The test results included a calibration specimen with linear stiffness and near zero hysteretic behavior that identified the capabilities and limitations of the procedure. Tension/compression pull tests of the truss joints were conducted. The load vs. displacement curves showed stiffness, deadband, and hysteresis loops consistent with theory. Vibration damping was inferred from the hysteresis loops and compared with measured data from a three bay truss.